2009
DOI: 10.1007/s11814-009-0184-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of pure ethanol from azeotropic solution by pressure swing adsorption

Abstract: There has been a gaining interest in the use of fuel ethanol from fermentation process. A main challenge in producing the ethanol concerned the production cost which was largely contributed by the process of water removal. Distillation could remove water to a certain level but due to ethanol-water azeotrope an extra process was needed before ethanol could be blended with gasoline. Problem statement: Pressure Swing Adsorption (PSA) process was attractive for final separation since it required less energy and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 10 publications
1
17
0
2
Order By: Relevance
“…Several research projects have been conducted using molecular sieves zeolites (Jeong et al, 2009;Pruksathorn and Vitidsant 2009;Simo et al, 2009;Carmo and Gubulin 2002) and biobased adsorbents (Boonfung and Rattanaphanee 2010;Beery et al, 1998) in PSA processes to dehydrate ethanol. For example, Simo and his co-workers (Simo et al, 2009) As it can be seen from Figure 2.1, water and ethanol is mixed with nitrogen gas (carrier gas) in the CEM (control-evaporation-mixing) unit, which is a vapor generating system.…”
Section: Pressure Swing Adsorption For Ethanol Dehydrationmentioning
confidence: 99%
“…Several research projects have been conducted using molecular sieves zeolites (Jeong et al, 2009;Pruksathorn and Vitidsant 2009;Simo et al, 2009;Carmo and Gubulin 2002) and biobased adsorbents (Boonfung and Rattanaphanee 2010;Beery et al, 1998) in PSA processes to dehydrate ethanol. For example, Simo and his co-workers (Simo et al, 2009) As it can be seen from Figure 2.1, water and ethanol is mixed with nitrogen gas (carrier gas) in the CEM (control-evaporation-mixing) unit, which is a vapor generating system.…”
Section: Pressure Swing Adsorption For Ethanol Dehydrationmentioning
confidence: 99%
“…The hybrid configurations of distillation with three extractive sequences were compared based on energy requirement and second law efficiency on the basis of similar feed and product specifications [9]. Several attempts were made to study and investigate bioethanol refining using molecular sieves and to investigate the effects of several operating parameters for process improvements [10,11,12,13]. Bioethanol refining was also studied using hybrid distillation-pervaporation process and the serially connected module was chosen as the best [14].…”
Section: Introductionmentioning
confidence: 99%
“…At present, ethanol fermentation technology generally employs batch bioreactor systems and only occasionally continues reactors where the cells are freely suspended in the liquid phase (Choi et al, 2009;Hong et al, 2009;Zhang et al, 2009;Turhan et al, 2010;Ghorbani et al, 2011;Li et al, 2010;Tang et al, 2010) in recent years, many workers have used immobilized-cell systems to ferment a wide variety of carbohydrates to ethanol (Liu et al, 2009;Singh et al, 2009;Pacheco et al, 2010;Ghorbani et al, 2011;Pruksathorn and Vitidsant, 2009) reported that certain strains of S. cerveisiae can undergo up to 10 fermentation cycles using molasses-containing medium. Alshiyab et al (2009) reported that by using bigger reactor size, the effect of gaseous products in fermentation medium was reduced and enhanced both bacterial productivity and biomass concentration, where Brethauer and Wyman (2010) reported that some continuous fermentations are now employed for commercial ethanol production from cane sugar and corn to take advantage of higher volumetric productivity, reduced labor costs, and reduced vessel down time for cleaning and filling.…”
Section: Discussionmentioning
confidence: 99%